On-Surface Synthesis of a π-Extended Diaza[8]circulene - Nakamura, Kimihiro (2021)
Heterocyclic [8]circulenes are an important class of polycyclic aromatic hydrocarbon molecules because of their unique structural properties and promising applications. However, the synthesis of heterocyclic [8]circulenes is still limited and thus is an important synthetic challenge. Here we describe the first example of a π-extended diaza[8]circulene surrounded by and fused with six hexagons and two pentagons, which was successfully synthesized only by a combined in-solution and on-surface synthetic strategy. State-of-the-art scanning tunneling microscopy with a CO-functionalized tip and density functional theory calculations revealed its planar conformation and unique electronic structure.